Case finding and screening clinical utility of the Patient Health Questionnaire (PHQ-9 and PHQ-2) for depression in primary care: a diagnostic meta-analysis of 40 studies - Mitchell, Alex J.; Yadegarfar, Motahare; Gill, John; Stubbs, Brendon (BJPsych open, 2016)
The Patient Health Questionnaire (PHQ) is the most commonly used measure to screen for depression in primary care but there is still lack of clarity about its accuracy and optimal scoring method. To determine via meta-analysis the diagnostic accuracy of the PHQ-9-linear, PHQ-9-algorithm and PHQ-2 questions to detect major depressive disorder (MDD) among adults. We systematically searched major electronic databases from inception until June 2015. Articles were included that reported the accuracy of PHQ-9 or PHQ-2 questions for diagnosing MDD in primary care defined according to standard classification systems. We carried out a meta-analysis, meta-regression, moderator and sensitivity analysis. Overall, 26 publications reporting on 40 individual studies were included representing 26 902 people (median 502, s.d.=693.7) including 14 760 unique adults of whom 14.3% had MDD. The methodological quality of the included articles was acceptable. The meta-analytic area under the receiver operating characteristic curve of the PHQ-9-linear and the PHQ-2 was significantly higher than the PHQ-9-algorithm, a difference that was maintained in head-to-head meta-analysis of studies. Our best estimates of sensitivity and specificity were 81.3% (95% CI 71.6-89.3) and 85.3% (95% CI 81.0-89.1), 56.8% (95% CI 41.2-71.8) and 93.3% (95% CI 87.5-97.3) and 89.3% (95% CI 81.5-95.1) and 75.9% (95% CI 70.1-81.3) for the PHQ-9-linear, PHQ-9-algorithm and PHQ-2 respectively. For case finding (ruling in a diagnosis), none of the methods were suitable but for screening (ruling out non-cases), all methods were encouraging with good clinical utility, although the cut-off threshold must be carefully chosen. The PHQ can be used as an initial first step assessment in primary care and the PHQ-2 is adequate for this purpose with good acceptability. However, neither the PHQ-2 nor the PHQ-9 can be used to confirm a clinical diagnosis (case finding). None. © The Royal College of Psychiatrists 2016. This is an open access article distributed under the terms of the Creative Commons Non-Commercial, No Derivatives (CC BY-NC-ND) licence.